Distinct Kynureninase and Hydroxykynureninase Activities in Microorganisms: Occurrence and Properties of a Single Physiologically Discrete Enzyme in Yeast - Shetty, A. S. (1973)
(i) Saccharomyces cerevisiae grown in the presence of 1.0 mM l-tryptophan slowly excreted fluorescent material that was chromatographically identifiable as 3-hydroxyanthranilate but did not excrete detectable amounts of anthranilate nor rapidly deplete the medium of l-tryptophan. Under similar growth conditions, Neurospora crassa rapidly excretes anthranilate and rapidly depletes the medium of l-tryptophan. (ii) Chromatographic analysis of crude extracts from yeast revealed a single kynureninase-type enzyme whose synthesis was not measurably affected by the presence of tryptophan in the medium. Previous studies have provided evidence for two kynureninase-type enzymes in N. crassa, an inducible kynureninase and a constitutive hydroxykynureninase. (iii) Kinetic analysis of the partially purified yeast enzyme provided Michaelis constants for l-3-hydroxykynurenine and l-kynurenine of 6.7 × 10(−6) and 5.4 × 10(−4) M, respectively. This and other kinetic properties of the yeast enzyme are comparable to those reported for the constitutive enzyme from N. crassa. (iv) These findings suggest that S. cerevisiae has in common with N. crassa the biosynthetic enzyme hydroxykynureninase but lacks the catabolic enzyme kynureninase. Therefore, it can be predicted that, unlike N. crassa, S. cerevisiae does not carry out the tryptophan-anthranilate cycle. Distinct kynureninase-type enzymes may exist in other microorganisms and in mammals.